Clustering of Regencies/Cities in NTT Province Based on Poverty Using the Ward and Fuzzy C-Means Methods - Ervi Dayana Putri; Tessy Octavia Mukhti (Jurnal MSA (Matematika dan Statistika serta Aplikasinya), 2026)
Poverty remains a major problem in Indonesia's economic development. In Indonesia, East Nusa Tenggara Province has the fifth highest percentage of poor people in Indonesia as of September 2024. However, East Nusa Tenggara Province has also shown a decline in its poverty rate. According to a report from the Statistics Indonesia of Nusa Tenggara Timur Province, 18.60 percent of the province's population will be impoverished in 2024. This number is still significantly higher than Indonesia's 8.57 percent poverty rate. Additionally, East Nusa Tenggara Province's districts and cities have not benefited equally from the reduction in poverty because of notable regional differences. This study uses poverty data for East Nusa Tenggara Province in 2024 obtained from the Statistics Indonesia of Nusa Tenggara Timur Province and applies cluster analysis by comparing the Ward hierarchical cluster method and the non-hierarchical Fuzzy C-Means method to group regions based on poverty characteristics. The results of the study concluded that the Ward method with 3 clusters provided better results than the Fuzzy C-Means method. It is anticipated that the government will use these results as a foundation to concentrate more on creating more focused development plans for regions with the highest rates of poverty.